Inclusive Education for the Deradicalization of Children Involved in Terrorism in Jakarta Juvenile Correctional Institution - Putri, Elizar Ayu; Nugroho, Fentiny; Sulhin, Iqrak (Technium Social Sciences Journal, 2024)
This paper focuses on the formulation of inclusive education for the deradicalization of children involved in terrorism in Jakarta Juvenile Correctional Institution. The institution is in charge of implementing the deradicalization programs for children involved in terrorism. However, research found that the deradicalization program for children involved in terrorism at Jakarta Juvenile Correctional Institution has yet succeeded in reforming the children to be law-abiding citizens. This study aims to formulate an inclusive education for the deradicalization of children involved in terrorism at Jakarta Juvenile Correctional Institution. This study is a qualitative study conducted at Jakarta Juvenile Correctional Institution. Research data was obtained through interviews, observations, focus group discussions, and literature reviews. The findings show that Jakarta Juvenile Correctional Institution implements non-formal education as a rehabilitation program for children involved in terrorism. The current non-formal education does not fully accommodate all the expected goals based on the outcome chain formulation within the framework of program theory. Adaptation and integration of non-formal education with other development programs is needed to support resistance to achieve correctional goals.